The Bright, Artificial Intelligence-Augmented Future of Neuroimaging Reading - Hainc, Nicolin; Federau, Christian; Stieltjes, Bram; Blatow, Maria; Bink, Andrea; Stippich, Christoph (Frontiers in Neurology, 2017)
Radiologists are among the first physicians to be directly affected by advances in computer technology. Computers are already capable of analysing medical imaging data, and with decades worth of digital information available for training, will an artificial intelligence one day signal the end of the human radiologist? With the ever increasing work load combined with the looming doctor shortage, radiologists will be pushed far beyond their current estimated 3 seconds allotted time-of-analysis per image; an artificial intelligence with super human capabilities might seem like a logical replacement. We feel, however, that artificial intelligence will lead to an augmentation rather than a replacement of the radiologist. The artificial intelligence will be relied upon to handle the tedious, time consuming tasks of detecting and segmenting outliers while possibly generating new, unanticipated results which can then be used as sources of medical discovery. This will affect not only radiologists, but all physicians and also researchers dealing with medical imaging. Therefore, we must embrace future technology and collaborate interdisciplinary to spearhead the next revolution in medicine.